Geomorphodynamics, evolution, and ecology of vertical roots - Heidelman, Martin; Vural, Dervis Can (Frontiers in Plant Science, 2023)
The roots of some coastal and wetland trees grow peculiar vertical protrusions, the function of which remains unclear. Here, using computational simulations based on first-principles fluid and sedimentation dynamics, we argue that the protrusions work together to create an elevated patch of sediment downstream of the tree, thereby creating its own fertile flood-protected breeding grounds for the seedlings. In our simulations, we vary the vertical root diameter, root spacing and total root area and show that there is an optimal vertical root spacing that depends on root thickness. Next, we quantify and discuss the cooperative effects between adjacent vertical root patches. Lastly, by varying vertical root spacing of a patch of trees, we estimate a maximal vegetation density for which vertical-root production has a beneficial geomorphological response. Our hypothesis suggests that vertical roots, such as the 'knee roots' of baldcypress trees, have an important role in shaping riparian geomorphology and community structure.